Hungary's crisis of democracy : the road to serfdom - Wilkin, Peter (2016)
Introduction: Hungary and the road to serfdom – Hungary in the modern world-system – Hungary, communism and the democratic transition – The evolution of Fidesz : from neo-liberals to conservative nationalists – Social movement protest 1 : the challenge of Jobbik – Digital governance and media wars : the battle for Hungary's media – Social movement protest 2 : Milla and virtual politics – The European Union, NATO and the Hungarian crisis – Conclusion : the road to serfdom revisited..